Filmes de óxido depositados em plasma de acetilacetonato de alumínio - Souza, Adriano Luiz da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Plasma de argônio modificado pela injeção de (0,80 g) de acetilacetonato de alumínio (AAA) foi utilizado para deposição de filmes sobre substratos de diferentes materiais. Foram investigados os efeitos do tempo de tratamento, potência de aplicação e concentração de O2 na atmosfera do plasma. Um reator de plasma de baixa pressão acoplado capacitivamente foi usado para produzir os filmes, com o pó de AAA acondicionado no centro do eletrodo inferior e os substratos acomodados ao seu redor. O processo de deposição dos filmes é dividido em 3 etapas em função do tempo de exposição a atmosfera do plasma. A primeira ocorre com Δt < 4 min, em que o etching é o processo de deposição dominante formando uma estrutura contendo óxidos de alumínio, grupos orgânicos e altos teores de hidróxidos de alumínio. Na segunda fase, a deposição é favorecida por uma alta densidade de fragmentos, por meio da sublimação do AAA (4 < t < 8 min) aumentando o conteúdo orgânico e reduzindo o conteúdo de hidróxido. A terceira fase ocorre com t > 8 min, etapa caracterizada por altas temperaturas e baixas pressões, devido ao esgotamento do composto precursor e conseguente remoção da camada depositada por meio dos gases resíduais, formando uma estrutura predominantemente oxidada. A redução do bombardeio iônico diminui a taxa de deposição e a espessura da camada, mas resulta em menor contaminação orgânica da estrutura que pode ser classificada como predominantemente composta por óxido de alumínio. No entanto, para tempos de processo mais longos, a supressão do bombardeio de íons não afeta a composição e a estrutura, mas afeta a morfologia do material resultante. A variação na proporção de oxigênio incorporado na atmosfera de deposição modifica a estrutura e morfologia dos filmes depositados. Enquanto nos plasmas com 25, 75 e 100% de O2 é formado um filme de óxido de alumínio, nos plasmas com 0% e 50% de O2, forma-se um oxicarbeto de alumínio hidrogenado com maior incorporação de defeitos. Os processos com 0% de oxigênio apresentam uma estrutura com direção cristalográfica preferencial, cuja intensidade é reduzida com a diminuição da proporção de Ar. O aumento da potência proporciona filmes com maior espessura, rugosidade e defeitos potencializados.

Oxide films were deposited using aluminum acetylacetonate (AAA) powder as precursor and plasma as deposition method. The objective of this work was to investigate the effect of the process time, the power of the excitation signal, the ionic bombardment and the O2% incorporated in the deposition atmosphere, varying from 0 to 100%, on the properties of the films obtained by means of sputtering reactive and AAA sublimation in pulsed direct voltage (DC) excited plasmas. For the production of the films, a capacitively coupled low pressure plasma reactor was used, with the AAA powder packed in the center of the lower electrode and the substrates accommodated around it. The plasma was established by applying a pulsed DC signal (-300 to -400 V, 20 kHz, 48/50 μs pulses) on the single electrode (sample holder) while the entire housing and top cover remained grounded. 3 series of deposition were carried out. The first investigated the effect of time. For this, the power was fixed at 400 W, the O2% at 50% and the time varied between 2 and 70 min. In the second series of experiments, the effect of ion bombardment was investigated by varying the polarization state of the samples and the time between 0 and 7 min. The plasma excitation power was kept at 400 W in these experiments. In the third series of experiments, he investigated the effect of oxygen proportion and excitation power, such that the deposition time was fixed at 4 min, the power varied between 400 and 500 W and the O2 proportion varied from 0 to 100%. The deposition time was fixed at 4 min and the power at 400 and 500 W. The layer thickness was obtained by means of a profilometer and the deposition rate as the ratio between thickness and deposition time. The molecular structure of the films was investigated using infrared spectroscopy techniques. The elemental composition was investigated by energy dispersive spectroscopy. The microstructure was investigated by scanning electron microscopy. Roughness was derived from topographic profiles acquired by profilometry. The process is divided into 3 phases depending on time. The first one occurs with t < 4 min, in which sputtering is the dominant deposition process, forming a structure containing aluminum oxides, organic groups and high contents of aluminum hydroxides. In the second phase, deposition is favored by a high fragment density and high AAA sublimation rates (4 < t < 8 min) increasing the organic content and reducing the hydroxide content. The third phase occurs with t > 8 min, a stage characterized by high temperatures and low pressures, favored by the depletion of the precursor compound that favors the removal of material from the deposited layer, forming a predominantly oxidized structure. Inhibition of ion bombardment reduces deposition rate and layer thickness, but results in less organic contamination of the structure which can be classified as predominantly composed of aluminum oxide. However, for longer process times, suppression of ion bombardment does not affect composition and structure, but does have an effect on the morphology of the resulting material. The variation in the proportion of oxygen incorporated into the deposition atmosphere modifies the structure and morphology of the deposited films. While in plasmas with 25, 75 and 100% of O2 an aluminum oxide film is formed, in plasmas with 0% and 50% of O2, a hydrogenated aluminum oxycarbide is created with greater incorporation of defects. The increase in power provides films with greater thickness, roughness and potentialized defects.
Oxide films deposited on aluminum acetylacetonate plasma
Keywords: tempo; Pulverização catódica; Estrutura; Etching; Time; Sputtering; Structure